Water recycling in Western Australia: analysis of 2003-2009 water quality monitoring programme - Shishkina, Natalia; Hannelly, Toni; Rodriguez, Clemencia (IWA Publishing, 2012)
Water-recycling schemes have been in operation in Western Australia since 1960. As a requirement of the regulatory framework for wastewater reuse, periodic water quality monitoring has been implemented to demonstrate microbial compliance for the intended end-use. For this study, we originally planned to analyse the compliance of the 92 water recycling schemes in the database over a 7 year period (2003–2009); however, it was necessary to exclude 21 schemes because they either lacked sufficient data or their recording standards were too inconsistent for the analysis. Compliance was analysed by comparing: (i) the observed microbial results against the quality criteria and (ii) the number of samples analysed against the expected number of samples based on regulatory frequency requirements. The results indicate that 12% of the remaining 71 schemes analysed did not comply with water quality criteria over the 7 year period, and most of the original 92 recycling schemes did not comply with the expected number of samples. Challenges faced by existing schemes in conforming to the Australian Guidelines for Water Recycling: Managing Health and Environmental Risks (Phase 1) (2006) and the Guidelines for the Non-Potable Uses of Recycled Water in Western Australia (2011) are discussed.